2022
DOI: 10.7759/cureus.27298
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Road Traffic Accidents Before and After the Implementation of a Seat Belt Detection System: A Comparative Retrospective Study in Riyadh

Abstract: IntroductionRoad traffic accidents (RTAs) are considered a major cause of death in Saudi Arabia. As seat belt compliance provides significant safety among drivers, a camera detection system has been implemented in March 2018 to enforce seat belt utilization, which can decrease the severity of road traffic injuries. There are no previous studies in the country that have assessed the effectiveness of a seat belt camera detection system on the severity of RTA-related injuries. MethodsA retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The age range of participants had no distractions. The mean age recorded was 30.13 (±12.86) years, 30.7 years, and 32.57 years, according to Alslamah, Thamer et al 2023 [20], Algahtany, Mubarak Ali 2022 [22], and Al Babtain, Ibrahim et al 2022 [24], respectively. AbdelRazik, Mohamed et al 2021 [23] reported that the age of 38% of cases was 20 to 30 years, and 23.3% were 30 to 40 years.…”
Section: Areamentioning
confidence: 94%
See 4 more Smart Citations
“…The age range of participants had no distractions. The mean age recorded was 30.13 (±12.86) years, 30.7 years, and 32.57 years, according to Alslamah, Thamer et al 2023 [20], Algahtany, Mubarak Ali 2022 [22], and Al Babtain, Ibrahim et al 2022 [24], respectively. AbdelRazik, Mohamed et al 2021 [23] reported that the age of 38% of cases was 20 to 30 years, and 23.3% were 30 to 40 years.…”
Section: Areamentioning
confidence: 94%
“…Socio-demographic characteristics of participants: The socio-demographic information of participants from nine distinct studies is included in Table 1, which summarises the large number of cases from references [20][21][22][23][24][25][26][27][28]. These studies' geographic scope is constrained because they were all selected within Saudi Arabia's regions, like the Aseer region [22], Al Kharj [23], Riyadh [24,26], Tabuk [25], Eastern Province [27], and Ha'il [28]. The research methodology of the reviewed studies [23,[25][26][27] used a cross-sectional design; one study [20] was Analysis of national data, and the others [21,22,24,28] were retrospective studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations